Study of the Cryopreservation Conditions for seed Materials of Chartolepis intermedia Boiss. - Ishmuratova Margarita (EDP Sciences, 2021)
For the first time, the depending of germination rate and energy of germination of Chartolepis intermedia seeds, collected in the wild of Karaganda region, from morphology of seeds and conditions of cryopreservation is investigated. The maximum results for viability are fixed for dark-colored average or large seeds. The best results are determined for variant of cryopreservation in plastic container with future defrosting at the room temperature. For the increasing parameters of seed germination we recommended to freeze Chartolepis intermedia seeds with using cryoprotector sucrose in concentration 20%. As the results of the study, we developed algorithm of cryopreservation of Chartolepis intermedia seeds in liquid nitrogen.